Executive function in paediatric medulloblastoma: The role of cerebrocerebellar connections. Issue 2 (4th August 2015) - Law, Nicole; Smith, Mary Lou; Greenberg, Mark; Bouffet, Eric; Taylor, Michael D.; Laughlin, Suzanne; Malkin, David; Liu, Fang; Moxon‐Emre, Iska; Scantlebury, Nadia; Mabbott, Donald
Abstract : Executive functions (EFs) are involved in the attainment, maintenance, and integration of information; these functions may play a key role in cognitive and behavioural outcomes in children treated for medulloblastoma (MB). At present, it remains unclear which EFs are most sensitive to the treatment effects for MB and whether damage to cerebrocerebellar circuitry is associated with EF. We completed a comprehensive evaluation of EF in 24 children treated for MB and 20 age‐matched healthy children (HC) and distilled these measures into components. Six components (C1–C6) were extracted from our model, reflecting dissociable constructs of EF: C1 = cognitive efficiency; C2 = planning/problem‐solving; C3 = positive cognitive emotion regulation; C4 = working memory; C5 = negative cognitive emotion regulation; and C6 = mixed cognitive emotion regulation. Group differences were found for C1, C2, C3, and C4; the MB group showed poorer performance on EF tasks and made less use of positive cognitive emotion regulation strategies relative to HC. Compromise to cerebrocerebellar microstructure – cerebro‐ponto‐cerebellar and cerebello‐thalamo‐cerebral pathways – was evident in children treated for MB compared to HC. We found that cerebrocerebellar circuitry has a mediating effect on one component of EF following treatment for MB – working memory.